Piperine Alleviates Doxorubicin-Induced Cardiotoxicity via Activating PPAR-γ in Mice. (17th December 2019) - Yan, Jie; Xu, Si-Chi; Kong, Chun-Yan; Zhou, Xiao-Yang; Bian, Zhou-Yan; Yan, Ling; Tang, Qi-Zhu
Abstract : Background . Oxidative stress, inflammation and cardiac apoptosis were closely involved in doxorubicin (DOX)-induced cardiac injury. Piperine has been reported to suppress inflammatory response and pyroptosis in macrophages. However, whether piperine could protect the mice against DOX-related cardiac injury remain unclear. This study aimed to investigate whether piperine inhibited DOX-related cardiac injury in mice. Methods . To induce DOX-related acute cardiac injury, mice in DOX group were intraperitoneally injected with a single dose of DOX (15 mg/kg). To investigate the protective effects of piperine, mice were orally treated for 3 weeks with piperine (50 mg/kg, 18:00 every day) beginning two weeks before DOX injection. Results . Piperine treatment significantly alleviated DOX-induced cardiac injury, and improved cardiac function. Piperine also reduced myocardial oxidative stress, inflammation and apoptosis in mice with DOX injection. Piperine also improved cell viability, and reduced oxidative damage and inflammatory factors in cardiomyocytes. We also found that piperine activated peroxisome proliferator-activated receptor- γ (PPAR- γ ), and the protective effects of piperine were abolished by the treatment of the PPAR- γ antagonist in vivo and in vitro. Conclusions . Piperine could suppress DOX-related cardiac injury via activation of PPAR- γ in mice.